Lacosamide cardiac safety: a thorough QT/QTc trial in healthy volunteers. (30th April 2015) - Kropeit, D.; Johnson, M.; Cawello, W.; Rudd, G. D.; Horstmann, R.
<x xml:space="preserve">Abstract</x> Objective To determine whether lacosamide prolongs the corrected QT interval (QTc). Materials and methods In this randomized, double‐blind, positive‐ and placebo‐controlled, parallel‐design trial, healthy volunteers were randomized to lacosamide 400 mg/day (maximum‐recommended daily dose, 6 days), lacosamide 800 mg/day (supratherapeutic dose, 6 days), placebo (6 days), or moxifloxacin 400 mg/day (3 days). Variables included maximum time‐matched change from baseline in QT interval individually corrected for heart rate ([HR] QTcI), other ECG parameters, pharmacokinetics (PK), and safety/tolerability. Results The QTcI mean maximum difference from placebo was −4.3 ms and −6.3 ms for lacosamide 400 and 800 mg/day; upper limits of the 2‐sided 90% confidence interval were below the 10 ms non‐inferiority margin (−0.5 and −2.5 ms, respectively). Placebo‐corrected QTcI for moxifloxacin was +10.4 ms (lower 90% confidence bound >0 [6.6 ms]), which established assay sensitivity for this trial. As lacosamide did not increase QTcI, the trial is considered a negative QTc trial. There was no dose‐related or clinically relevant effect on QRS duration. HR increased from baseline by ~5 bpm with lacosamide 800 mg/day versus placebo. Placebo‐subtracted mean increases in PR interval at tmax were 7.3 ms (400 mg/day) and 11.9 ms (800 mg/day). There were no findings of second‐degree or higher atrioventricular block. Adverse events (AEs) were dose related and most commonly involved the nervous and gastrointestinal systems. Conclusions Lacosamide (≤800 mg/day) did not prolong the QTc interval. Lacosamide caused a small, dose‐related increase in mean PR interval that was not associated with AEs. Cardiac, overall safety, and PK profiles for lacosamide in healthy volunteers were consistent with those observed in patients with partial‐onset seizures.